Concussion Recovery in Children and Adolescents: A Qualitative Study of Parents' Experiences. (21st November 2021) - Sullivan, Lindsay; Wysong, Matthew; Yang, Jingzhen
ABSTRACT: BACKGROUND: Although parents play an instrumental role in youth concussion management, few studies have qualitatively explored youth concussion recovery from the parents' perspective. This study explored parents' experiences with and perceptions of their child's recovery from concussion, particularly with regards to the return‐to‐school process. METHODS: We conducted 11 face‐to‐face semi‐structured interviews with the parents of concussed youth aged 11 to 17 years between October 2018 and April 2019. We used the methods of open coding, axial coding, and selective coding to analyze the data. RESULTS: We identified 7 themes during data analysis, which we divided into 2 categories: at home (prior to school re‐entry) and at school (during the school reintegration process). The at‐home category included 4 themes: (1) physical and cognitive rest; (2) child‐led decision‐making; (3) the role of parent‐child communication in recovery; and (4) feelings about returning to school following concussion. The at‐school category included 3 themes: (1) availability and utilization of academic accommodations; (2) return‐to‐school policies and procedures; and (3) support from school officials and teachers. CONCLUSIONS: Parents' experiences of their child's return‐to‐school post‐concussion underscore the need for evidence‐based guidelines for cognitive rest post‐concussion and a collaborative, team‐based approach to concussion management.